Tinjauan terhadap Layanan Perpustakaan Keliling pada Perpustakaan Umum Gunung Bungsu Kabupaten Tanah Datar - Arismen, Arismen; Syahyuman, Syahyuman (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
Writing this paper aims to determine: 1) How bookmobile service at Public Library Mt youngest Tanah Datar, 2) lack of efficiency factor inhibitors bookmobile service at Public Library Mt youngest Tanah Datar, 3) efforts to solve the problem in a mobile library service in Public Library of Mount youngest Tanah Datar. Data were collected through direct observation when the Job Training and interview with one of the officers of Public Library of Mount youngest Tanah Datar. Deskriptif.Berdasarkan data analysis conducted data analysis, Public Mobile Library Car Mount Youngest mostly located in front of the school near the public library. This is not in accordance with the purpose of a mobile library to provide services primarily in the general population that are out of range. And services around the Library General Mountains youngest is still too short is 2 hours each postal service and run only 2 times in 1 week. Keywords: services; bookmobile service